65/65=1+65=66

66 times 6 equals 396.

66 plus 66 equals 132

18 + 10 + 28 + 10 = 66

96

26

144

144

x = 10

If I am correct, 9 plus 7 equals 112.

66

144, you add the plus numbers, then multiply it by the first.

144, you add the plus numbers, then multiply it by the first.

1+2+3+... +65 = 65*66/2 = 65*33 = 2145 For the required sum, each term is simply double the corresponding term above, so 2+4+6+... + 130 = 2*2145 = 4290

144 9+7 = 16 and 9*16 = 144

273 13+8 = 21 and 13*21 = 273

66.

2+3 = 5 * 2 = 10. 7+2 = 9 * 7 = 63.6+5 = 11 * 6 = 66.x+y = z * x = n.9+7 = 16 * 9 = 144

144 9+7 = 16 and 9*16 = 144

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. Generally, x plus y = x(x+y).

then 4 plus 3 equals 28 and 3 plus 3 equals 18 and 7 plus 5 equals 84 .... its easy you just have to multiply the answer with the first number.. for example : 2 plus 3 equals 5 but when you multiply the answer with the first number (2) it becomes equals 10, and so on the others..

639.